Display activity and foraging costs of a frugivorous lekking bird - Cestári, César; Pizo, Marco Aurélio [UNESP]; Loiselle, Bette A. (Taylor & Francis, 2018)
Sexual success of males in lek breeding systems is often determined by display activities that require high energetic costs and may represent honest signals of male quality to females. In this context, manakins (Aves, Pipridae) evolved behavioral, morphological, and physiological adaptations that enable complex display maneuvers, and a high rate of fruit ingestion is needed to cope with the energetic costs of lekking activities. We examined the relationship between different displays (rolled-snaps, flights-down, and snap-jumps) and fruit consumption (a proxy for energy intake) by White-bearded Manakin males (Manacus manacus). We conducted a fruit supplementation experiment and recorded male displays in 23 arenas on 5 leks in southeastern Brazil. The flight-down was the display most related to fruit consumption (and energy refueling) by males of the White-bearded Manakin. This display seems to be decisive to the mating success of Manacus males; once inside a lek area, females are driven to display arenas by flights-down of males as an obligatory stage before copulation. This study opens a promising avenue for further field experiments designed to test how local food resources differentially impact display behavior among males in leks.
Keywords: frugivory; leks; male display; Manacus; sexual selection